Development and evaluation of double genes targeted multiplex PCR assays for the determination of bovine, buffalo and porcine materials in food products / M. A. Motalib Hossain - M. A. Motalib, Hossain (2017)
Bovine, buffalo and porcine materials in food products are sensitive to religions and a big threat to health and fair economic practices. Current methods to authenticate these animal materials in food chain are based on mainly single gene target which are generally longer in length and thus breakdown during food processing treatments. For the first time, here I targeted double gene sites in short-amplicon length multiplex polymerase chain reaction (mPCR) assays for the detection and differentiation of bovine, buffalo and porcine materials in food chain. Multiple targets detection in single assay saves analytical cost and time. Both the conventional and real-time PCR platforms were developed and authentic target detection was confirmed through sequencing and Restriction Fragment Length Polymorphism analysis. Mitochondrial cytochrome b (cytb) and NADH dehydrogenase subunit 5 (ND5) genes were targeted and six different targets (length: 73-146 bp), two for each of cow (121 and 106 bp), buffalo (90 and 138 bp) and pig (73 and 146 bp), were amplified from raw, boiled, autoclaved and microwaved cooked meat under pure and mixed matrices. The specificity of the PCR assays were checked against three targets and 25 non-target species. Specific PCR products were found only from beef, buffalo, and pork that were targeted in this assay. To eliminate the possibility of any false-negative detection, eukaryotic endogenous control was used for specificity testing. The detection limit was 0.01 ng DNA for tetraplex and 0.02 ng DNA for hexaplex under pure states and 0.1% target meat in mixed and commercial matrices. Complete sequence matching was found for five the PCR products but 98.5% for buffalo ND5 gene. The PCR products were digested by four restriction enzymes, namely AluI, EciI, FatI and CviKI-1 and clear restriction fingerprints were obtained. The developed methods were used for the screening of bovine, buffalo and porcine materials in various commercial meat curries and processed foods, namely, meatballs and frankfurters. Survey results revealed about 80% of beef meatballs were adulterated with buffalo and about 20% of beef products were totally replaced with buffalo. Moreover, the analysis of 20 beef frankfurters revealed the presence of both beef and buffalo in all specimens. This demonstrated that all beef frankfurter products are adulterated with buffalo in Malaysia. However, the analysis of 7 beef curries reflected only 2 them were beef and 5 were buffalo. In contrast, porcine meatball and frankfurter were found 100% authentic and also no pork was detected in halal branded beef curries, meatballs and frankfurters and chicken frankfurters. Finally, the developed TaqMan probe multiplex real-time PCR (mqPCR) assay successfully detected 0.003 ng DNA in a pure state and 0.1% target meat in mixed and commercial matrices. Analysis of commercial products under mqPCR assay revealed 71% and 100% of beef frankfurters, meatballs and 85% burgers contained buffalo adulteration but no pork in Malaysian markets. The advantage of the method was evidenced in terms of fidelity, cost and time since all the three species were detected and the option of alternative targets could complement missing targets even in decomposed specimens.